(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article highlights the manifestation of the center and subordinate relationship at the syntactic level and the hierarchy of components, especially in compound sentences. The phenomenon in Turkish languages - the transformation of a sentence into one nominative unit and the occurrence of one constructive clause or an expander of one constructive clause in another sentence is analyzed. One of the syntactic-structural features characteristic of the grammar of the Uzbek language- the issue of the transformation process in the hierarchy of sentence fragments and the status of the sentence and word expander in the hierarchy are clarified in stepwise syntactic analysis. The position of the actants at the level of sentence construction is clarified by analyzing the connection of words in the LSQ of the sentence, the issue of semantic and grammatical connection between the parts (components) of the linguistic sentence at the language stage of the sentence is clarified.